Pemikiran Ekonomi Ibnu Taimiyah Dan Relevansinya Terhadap Ekonomi Modern - Iin Natasya Divana Ginting; Abdul Rozaq Wall; Diska Najwa Andini; M. Ikhsani Simanjoran (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Human life cannot be separated from economic problems that affect human relationships with other humans. These relationships must be based on Islamic religious norms which regulate all aspects of life, including those related to muamalah issues. As part of our efforts to develop an Islamic economic system, we are trying to find a concept of the main ideas of that time as inspiration and guidance. For this reason, the author tries to convey the main thoughts of one of the scholars, namely: Shaykhul Islam Ibn Taimiyah which relates to economic issues, he has very in-depth knowledge about Islamic teachings. Islam today requires a clear economic perspective regarding what is expected and how these things can be achieved. To achieve these rights requires freedom in the economy and property rights limited by moral law and supervised by a state that is just and capable of enforcing sharia law. All economic activities are permitted unless the activity is expressly prohibited by the Shari'a.